Study on the Marketing Services in Corporate Sector: Exploring fuel consumer behavior and loyalty towards oil marketing companies (Journal of Advances and Scholarly Researches in Allied Education, 2018)
One particular customer behavior that has intrigued the marketers and researchers for long has been the indifference exhibited by fuel consumers while making choice amongst these three brands to refuel their vehicles. This research aims to study the brand position and customer loyalty for public sector oil marketing companies. The results point towards an opportunity which the oil marketing companies have to increase the brand position and customer loyalty by devising income wise segmentation strategies for different consumer groups.